2021
DOI: 10.1007/s00520-021-06066-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of taste alterations in people receiving taxane-based chemotherapy and their association with appetite, weight, and quality of life

Abstract: Purpose There is limited evidence on the effect of chemotherapy-associated taste alteration. This study aimed to evaluate taste alteration characteristics in patients receiving taxane-based chemotherapy and investigate the association of taste alterations with appetite, weight, quality of life (QOL), and adverse events. Methods This cross-sectional study evaluated 100 patients receiving paclitaxel, docetaxel, or nab-paclitaxel as monotherapy or combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…Taste and/or smell are not altered in BC patients before CT [ 14 ]. In BC subjects under CT, the prevalence and incidence of dysgeusia are both highly variable, ranging respectively from 59% to 83% [ 15 , 16 , 17 ] and from 53% to 97.3% [ 7 , 18 ] ( Table 1 ). Possible reasons for these differences are described below.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Taste and/or smell are not altered in BC patients before CT [ 14 ]. In BC subjects under CT, the prevalence and incidence of dysgeusia are both highly variable, ranging respectively from 59% to 83% [ 15 , 16 , 17 ] and from 53% to 97.3% [ 7 , 18 ] ( Table 1 ). Possible reasons for these differences are described below.…”
Section: Resultsmentioning
confidence: 99%
“…Although all antineoplastic drugs have been associated with some degree of taste alterations, an observational study conducted in 151 cancer patients (35% with BC) undergoing CT reported anthracyclines, paclitaxel, carboplatin, and docetaxel as the CT agents producing the highest taste disturbance rates, while the use of cisplatin and 5-fluorouracil resulted in the lowest complaints [ 19 ]. Taxane-based therapies were reported to cause more severe dysgeusia, both in all cancers and in BC [ 17 , 20 ], with a prevalence of 75–93% in the former and 81.5% in the latter [ 17 ]. Two multicenter, phase III, randomized trials compared adjuvant cyclophosphamide, methotrexate, fluorouracil (CMF) with docetaxel (DXL) chemotherapy in ≥65-yo BC patients [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Em geral, a redução do paladar ou o aumento da sensibilidade a alguns sabores pode reduzir a massa corporal e a qualidade de vida dos pacientes devido à redução da ingestão de alimentos. O impacto das alterações do paladar no peso corporal e na qualidade de vida em sido recentemente abordado na literatura de TCH (Cohen et al, 2016;Ponticelli et al, 2017;Abasaeed et al, 2018;Barban et al, 2020;Ferreira et al, 2020;Kaizu et al, 2021).…”
Section: Alteração De Paladar No Transplante De Células Hematopoiéticasunclassified